2016
DOI: 10.4186/ej.2016.20.5.169
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Conventional and Variable Frequency Microwave Curing of SU8 Photoresist: Effects on the Dielectric, Thermal, and Morphological Properties

Abstract: Abstract. Variable Frequency Microwave (VFM) is known to be a rapid, volumetric, and selective form of heating which has shown potential as an alternative technique for the processing of negative-tone SU8 photoresist in the Micro-Electro-Mechanical System (MEMS) industry. A comparison of thermal properties of the films cured during the softbake and post exposure bake process using different techniques, i.e. conventional thermal curing, VFM curing, and a combination of both (referred to as hybrid, HY), was inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
(50 reference statements)
0
2
0
Order By: Relevance
“…Kuebler et al showed that pre-exposure solvent content as low as 1 wt.-% causes features in woodpile structures to become rounded and less well resolved, whereas reducing solvent content down to 0.68 wt.-% yielded higher resolution structures with more sharply defined features [ 50 , 55 ]. While hot-plate heating is typically employed, alternative heating methods like IR and frequency variable microwave heating can also be used to reduce heating times and achieve lower solvent contents [ 56 , 57 ]. Convection oven heating is not recommended, because a skin of dry resin will form at the interface with air, which limits the vaporization of the solvent.…”
Section: Su-8 As a Materials System For Mplmentioning
confidence: 99%
“…Kuebler et al showed that pre-exposure solvent content as low as 1 wt.-% causes features in woodpile structures to become rounded and less well resolved, whereas reducing solvent content down to 0.68 wt.-% yielded higher resolution structures with more sharply defined features [ 50 , 55 ]. While hot-plate heating is typically employed, alternative heating methods like IR and frequency variable microwave heating can also be used to reduce heating times and achieve lower solvent contents [ 56 , 57 ]. Convection oven heating is not recommended, because a skin of dry resin will form at the interface with air, which limits the vaporization of the solvent.…”
Section: Su-8 As a Materials System For Mplmentioning
confidence: 99%
“…Furthermore, microwave curing has also been known as an environmental-friendly technology due to its characteristics such as higher cross-linking rate, shorter reaction time, the reduction of hazards and pollution, better heat uniformity and higher product yield compared to conventional thermal curing. [16,17] According to the literature, a number of studies have reported the cross-linking of chitosan film using different cross-linkers and curing methods. [11,[18][19][20] However, to the best of our knowledge, there are no studies comparing of the influence of different cross-linking methods on the properties of CNC/chitosan film composites.…”
Section: Introductionmentioning
confidence: 99%